ASPEK HUKUM DALAM EKONOMI MENGENAI ANTI MONOPOLI DAN PERSAINGAN TIDAK SEHAT - Rusniati, Rusniati (Disiplin : Majalah Civitas Akademika Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2022)
Monopoly practice is a concentration of economic power by one or more actors that results in the control of the production and marketing of certain goods or services, which results in obsolete competition, unfair competition is competition between entrepreneurs who carry out activities of production or marketing of goods and services in a way that is unfair, against the law, or hinder the competition of enterprises. In accordance with article 1, paragraph (2)-activities prohibited: (a) Monopoly, (b) Monopsony, (c) Market domination, (d) Concerns, (e) Dominant positions, (f) Department of Invasion, (g) Non-compliant ownership of shares, (h) Mergers, mergers, and non-procedural acquisitions. Forbidden treaties: (a) Oligopoly, (b) Pricing, (c) Territorial division, (d) boycott, (e) cartels, (f) trusts, (g) oligopolies, (h) vertical integration, (i) closed agreements, (j) agreements with foreigners.